Yoga: As a Transformative Approach to Addressing Male Infertility and Enhancing Reproductive Health in Men: A Narrative Review - Anjali Yadav; Prabhakar Tiwari; Rima Dada (Journal of Human Reproductive Sciences)
Infertility presents multifaceted challenges that encompass both physical and emotional burdens. Yoga, as a comprehensive system of mind–body medicine, serves as an effective intervention for managing male factor infertility, a complex lifestyle disorder with significant psychosomatic elements. This review explores the transformative role of yoga in addressing both the emotional and physical dimensions of infertility. By incorporating physical postures, breath control and meditation, yoga promotes emotional well-being and enhances reproductive health by improving the integrity of nuclear and mitochondrial genomes as well as the epigenome. In addition, yoga contributes to maintaining sperm telomere length through the regulation of seminal free radical levels and increased telomerase activity, which are crucial for optimal embryo cleavage and the development of high-quality blastocysts. Integrating yoga as an adjunctive therapeutic approach fosters a supportive intrauterine environment and facilitates physiological homoeostasis, thereby increasing the likelihood of successful fertilisation and implantation. Gentle asanas and flowing sequences promote relaxation, alleviate tension and cultivate emotional stability, while meditation aids in emotional healing and resilience during the infertility journey. Specific asanas, such as Baddha Konasana (bound angle pose), Bhujangasana (cobra pose) and Sarvangasana (shoulder stand), stimulate reproductive organs, enhance blood circulation and regulate hormone production. Pranayama techniques further support endocrine balance and overall vitality. Moreover, yoga provides a non-invasive strategy for managing fertility-related conditions leading to improved reproductive health and overall well-being. This review aims to elucidate the comprehensive role of yoga in improving male infertility, focusing on its impact on sperm nuclear and mitochondrial genomes, the epigenome and telomere health. In addition, it underscores the importance of self-care, open communication and shared experiences with partners. Practicing yoga regularly supports psychosocial well-being, promotes holistic healing, enhances physical and mental health and probably helps in improving reproductive health, thereby fostering resilience and self-efficacy throughout the journey of fertility and reproduction.